Historical and ethical issues in trial design - Matthews, J. Rosser (Henry Stewart Talks, 2018)
Historical antecedents to the clinical trial, Pharmacology & mathematical statistics as key for clinical trials, Shortage of streptomycin during WWII & use of control groups, Unethical research studies & informed consent by study subjects, Withholding a potentially useful therapy, Letting chance determine patient assignment, Advancing scientific knowledge without reducing study participants to a means to an end, General ethical frameworks of Utilitarianism & Kantianism, Eight factors to be considered in designing ethical and scientific studies